Zinc (II) modified hydroxyapatites for tetracycline removal: Zn (II) doping or ZnO deposition and their influence in the adsorption. (15th January 2021) - Oliveira, Cleibson; de Oliveira, André L. Menezes; Chantelle, Laís; Landers, Richard; Medina-Carrasco, Santiago; Del Mar Orta, María; Silva Filho, Edson C.; Fonseca, Maria G.
Graphical abstract: Zn(II) modified hydroxyapatites were successfully prepared via a new route combining the co-precipitation/impregnation over microwave heating using casein as template. The structural characterizations revealed the formation of Zn-doped HAp/ZnO-type composites. The presence of Zn 2+ /ZnO rendered the modified hydroxyapatites suitable for tetracycline removal. Highlights: Zn-hydroxyapatite/ZnO nanoparticles was obtained by co-precipitation/microwave method. Casein was used as template in the preparation zinc (II) modified hydroxyapatites. Formation of the Zn-HAp/ZnO was confirmed by structural and morphological techniques. Tetracycline adsorption by Zn-HAp/ZnO composites was dependent of the ZnO content. Maximum adsorption capacity was 168.46 mg L −1 in 20 min. Abstract: Zn(II) modified hydroxyapatites were prepared through the microwave-assisted co-precipitation/hydrothermal method using zinc acetate and HAp in the presence of casein as the template, followed by calcination at 500 °C in an oxygen atmosphere with the heating rate of 2 °C min −1 for 12 h. The zinc acetate proportion in relation to the mass of pure HAp was varied to obtain theoretical final products with 5%, 10%, and 20% ZnO, which were labeled as HAp/ZnO-1, HAp/ZnO-2, and HAp/ZnO-3, respectively. The synthesized solids were then characterized using X-ray diffraction, Fourier transform infrared spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy, X-ray dispersive spectroscopy, and nitrogen adsorption/desorption isotherm measurements. The adsorptive properties of the materials for the removal of tetracycline (TC) from aqueous solutions were evaluated using the Langmuir, Freundlich, and Temkin isotherm models. The structural characterizations revealed the formation of Zn-doped HAp/ZnO-type composites. The samples rich in ZnO (HAp/ZnO-3) exhibited good TC removal efficiency with a maximum adsorption of 168.5 mg L −1 within 20 min. The adsorption capacity data of the samples could be well-fitted to the Langmuir model. The ZnO content played an important role in adjusting the adsorptive properties of HAp for applications in wastewater treatment, especially for the removal of drugs from aqueous solutions.